THE QUANTITY COMPONENT OF ABSOLUT LEUKOCYTE COUNT OF MICE (Mus musculus L) AS BIOLOGICAL INDICATORS CO-60 GAMMA RADIATION - Sutapa, Ngurah; Soejoko, Djarwani; Sudarsana, Balik (Jurnal Biologi Udayana; Vol 16 No 1 (2012): Jurnal Biologi)
The purpose of this study was to calculate the absolute quantity of leucocytes components of mice ( Mus musculus L.) as a biological indicator of Co-60 gamma ray.  The sample of mice were grouped into 4: control; treated with Co-60 gamma ray without adaptation; treated with Co-60 gamma ray with adaptation I and treated with Co-60 gamma ray with adaptation II.  In the treatment without adaptation, mice were treated with the doses of 1.0, 1.5, 2.0, 2.5 dan 3.0 Gy.  In adaptation I, mice were adapted with radiation 0.1 Gy. Just before treated with the challenge doses and in adaptation II, the challenge doses was applied 5 hours after the mice adapted with the radiation of 0.1 Gy.  The average number of mice leucocytes in control treatment was eosinophil, rod neutrophil, segmented neutrophil, lymphocyte, and monocyte, respectively.  As a result of the radiation treatments, the number of leucocytes decreased.  The number of segmented neutrophil and lymphocytes decreased as the dose increases, while the number of eosinophil, rod neutrophil and monocytes did not significantly different among three treatments.  Therefore, the components of segmented nuetrophil and lympohocyte can be employed as a biological indicator of gamma Co-60 radiation.
Keywords: absolute count, leukocyte components, biological indicators